Handbook of Climate Change Resilience - Walter Leal Filho (2020)
Climate resilience, or the capacity of socio-ecological systems to adapt and upkeep their functions when facing physical-chemical stress, is a key feature of ecosystems and communities. As the risks and impacts of climate change become more intense and more visible, there is a need to foster a broader understanding of both the impacts of these disruptions to food, water, and energy supplies and to increase resilience at the national and local level. The Handbook of Climate Change Resilience comprises a diverse body of knowledge, united in the objective of building climate resilience in both the industralised and the developing world. This unique publication will assist scientists, decision-makers and community members to take action to make countries, regions and cities more resilient.